A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam - van Tri, Ngo; Grismer, L. Lee; Thai, Pham Hong; Wood, P.l. Jr (Zootaxa, 2020)
A new species of insular Bent-toed Gecko, Cyrtodactylus culaochamensis sp. nov. of the C. irregularis group is described from Cu Lao Cham Mountain, from Hon Lao Island, Hoi An City, Quang Nam Province, Cham Islands, central Vietnam. Cyrtodactylus culaochamensis sp. nov. is the sister species of C. pseudoquadrivirgatus from Ba Na Nui Chua from Danang City, central Vietnam. It differs from all congeners by having a maximum SVL of 79.8 mm (n=5); dark spots on the head edged in white; a fragmented nuchal loop; irregularly shaped, broad, completed or broken dorsal bands; 19–21 interorbital scales across the frontal bone; 28–32 scales between the eye and nostril; 45–50 rows of ventral scales between the ventrolateral folds; scattered, smooth tubercles; 20–22 irregular, longitudinal rows of weakly keeled tubercles at midbody between the ventrolateral folds; seven or eight precloacal pores in a chevron pattern in males; no enlarged femoral scales, no femoral pores; 13–15 subdigital lamellae on first toe; 20–23 subdigital lamellae on fourth toe; and very slightly enlarged subcaudal scales.